Validation and reliability of reflux symptoms score-12 in Bahasa Malaysia - Sobani, Muhamad Ariff; Mansor, Masaany; Rajendram, Nesha; Mat Barhan, Noor Shairah; Abdullah, Nik Nairan (Faculty of Medicine, 2025)
Laryngopharyngeal reflux is a prevalent disease. The combined multichannel intraluminal impedance and pH monitoring device is the “gold standard” to diagnose LPR but only available in certain centres. Primary care givers should be equipped with tools applicable everywhere to diagnose and monitor LPR efficiently such as the Reflux Symptoms Score 12 (RSS-12).This study was conducted to develop a Malay version of RSS-12 and to evaluate validity, consistency and reliability of this tool to be applied to the Malaysian population. The English RSS-12 was adapted into Bahasa Malaysia Reflux Symptom Score 12 (M-RSS 12) translated to Bahasa Malaysia by an authorized translator. Content validation was done by 3 expert panels. Face validation performed using the questionnaire rated by 10 respondents from our clinic. A pilot study involving 30 patients was then conducted to determine the feasibility of the study. The item-level content validity index (I-CVI) for all items was 1.0, the scale-level content validity index (S-CVI/Ave) was 1. The item-level face validity index (I-FVI) for all items was 0.95 -1.00 and scale-level face validity index based on the average method (S-FVI/Ave) was 0.99. Both indices of content validity and face validity achieved satisfactory level. For internal consistency, the Cronbach alpha for 3 domains in the MRSS-12 ranged between 0.891-0.928 which showed high reliability. M RSS-12 is practical, valid and reliable to be used among Malaysian population.